Rethinking professional governance international directions in healthcare - Kuhlmann, Ellen 1957-; Saks, Mike 1952- (Policy Press, 2008)
This original and innovative book opens up new perspectives in health policy debate, examining the emerging international trends in the governance of health professions and the significance of national contexts for the changing health workforce. In bringing together research from a wide range of continental European countries as well as the United Kingdom, Canada and Australia, the contributors highlight different arenas of governance, as well as the various players involved in the policy process. They expand the public debate on professional governance - hitherto mainly limited to medical self-regulation - to encompass a broad span of health care providers, from nurses and midwives to alternative therapists and health support workers. The book provides new data and geopolitical perspectives in the debate over how to govern health care. It helps to better understand both the enabling conditions for, and the barriers to, making professionals more accountable to the interests of a changing public. This book will be a valuable resource for students at an undergraduate and postgraduate level, particularly for health programmes, sociology of professions and comparative health policy, but also for academics, researchers and managers working in health care